Analisis Daya Dukung Lahan Pertanian di Desa Penyangga Kawasan Ekonomi Khusus Mandalika - Kabupaten Lombok Tengah - Candra Ayu; Wuryantoro Wuryantoro; Nurtaji Wahoni; Ibrahim Ibrahim; Eka Nurminda Dewi Mandalika (Universitas Mataram, 2023)
The Mandalika Special Economic Zone in Central Lombok Regency plays a role in accelerating the distribution of national economic development in the region and strengthening the economy of the surrounding village communities. This study aims to analyze the carrying capacity of food crop farming land to farmer households in the buffer village of the Mandalika Special Economic Zone. The research method is descriptive and data collection using survey techniques. The research location is in the food crop center supporting villages (Sengkol, Rembitan and Sukadana villages) and the respondents are 45 farmers. (criteria for poverty in Sajogyo and the World Bank) and technical support using the Carrying Capacity Ratio formula. The results showed that the economic carrying capacity equivalent to rice was 312.52 kg/capita/year or US 0.55/capita/day and the welfare of farmers was classified as poor. The contribution of economic carrying capacity to the ability to fulfill staple food of farmer households is 65.11%. The carrying capacity of the land is technically high (CCR=1.99) so that the land is still able to: support the life of the population and receive additional population, as well as the development of food crop agriculture which is expansive and explorative in nature. Each farming household can have a planting area that is 1.2 ha larger than the average land ownership. Farming households can own a planting area of ​​1.2 ha larger than their average land ownership. In order for the carrying capacity of food crop farming land to prosper farmers, it is necessary to develop expansive and exploratory land, especially in the dry season and limit the conversion of agricultural land to food crops due to population growth in the buffer villages of KEK Mandalika - NTB.